The fMRI BOLD response to unisensory and multisensory smoking cues in nicotine-dependent adults. Issue 3 (30th December 2015) - Cortese, Bernadette M.; Uhde, Thomas W.; Brady, Kathleen T.; McClernon, F. Joseph; Yang, Qing X.; Collins, Heather R.; LeMatty, Todd; Hartwell, Karen J.
Abstract: Given that the vast majority of functional magnetic resonance imaging (fMRI) studies of drug cue reactivity use unisensory visual cues, but that multisensory cues may elicit greater craving-related brain responses, the current study sought to compare the fMRI BOLD response to unisensory visual and multisensory, visual plus odor, smoking cues in 17 nicotine-dependent adult cigarette smokers. Brain activation to smoking-related, compared to neutral, pictures was assessed under cigarette smoke and odorless odor conditions. While smoking pictures elicited a pattern of activation consistent with the addiction literature, the multisensory (odor+picture) smoking cues elicited significantly greater and more widespread activation in mainly frontal and temporal regions. BOLD signal elicited by the multisensory, but not unisensory cues, was significantly related to participants' level of control over craving as well. Results demonstrated that the co-presentation of cigarette smoke odor with smoking-related visual cues, compared to the visual cues alone, elicited greater levels of craving-related brain activation in key regions implicated in reward. These preliminary findings support future research aimed at a better understanding of multisensory integration of drug cues and craving. Highlights: Drug-related odors play a significant role in drug craving. Picture-odor drug cues elicited more craving-related activation than pictures alone. Additional study regarding sensory processing/integration of drug cues is warranted.